The emergence of mRNA therapeutics: A new era in precision medicine - Sachin Sakat, Aditi Jyotishi, Bindurani LGP Ram, Ajay Kharche, Swati Mutha, Vimla Chaudhari, Satish Dhonde, Shivraj Dhage (Journal of Applied Pharmaceutical Science, 2025)
Messenger RNA (mRNA) therapeutics have become a revolutionary means of modern medicine with extensive popularity with the expedited development of COVID-19 vaccines. Apart from vaccines, mRNA technology is potentially of vast importance for cancer immunotherapy, monogenic disorder treatments, regenerative medicine, and gene editing. Over 150 mRNA-based treatments are under different stages of clinical trials currently, with substantial advances being made in oncology, where mRNA cancer vaccines have shown progression-free survival advantages of up to 44% with combined therapies. Lipid nanoparticle-encapsulated mRNA medicines have shown more than 50% restoration of missing protein levels with preclinical studies for the treatments of rare genetic diseases. Even with such advances, hurdles exist for optimizing delivery approaches, achieving prolonged protein expression, and subduing immune activation. This review outlines mechanisms of mRNA therapeutics, active clinical advancements, as well as upcoming advances such as self-amplifying mRNA as well as in vivo gene editing. As technological refinements continue, mRNA therapeutics are poised to revolutionize personalized medicine across a broad spectrum of diseases.
Keywords: mRNA, vaccine, lipid nanoparticles, methylmalonic acidemia, cystic fibrosis, SARS-CoV-2, COVID-19 vaccines